رخصة البناء كآلية للتخطيط العمراني الحديث في الجزائر (دراسة على ضوء أحكام المرسوم التنفيذي 15/19 المتعلق بعقود التعمير المعدل والمتمم) A building permit is a tool for modern urban planning in Algeria (A study in light of the provisions of Executive Decree - سلطاني عبد العضيم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
شهد التطور العمراني في الجزائر في السنوات الأخيرة حركية كبيرة بسبب تزايد النمو الديمغرافي، الأمر الذي ادى إلى تشويه النسيج العمراني وانتشار البناءات الفوضوية، الامر الذي حذا بالمشرع الجزائري الى سن أدوات وآليات لضبط هذا الامر، ومن اهم هذه الاليات رخصة البناء والتي تعتبر من اكثر الوسائل نجاعة وفعالية في تنظيم عمليات البناء و الحفاظ على النسيج العمراني وحماية البيئة من كل المخاطر الناتجة عن سوء التخطيط العمراني. The urban development in Algeria in recent years has witnessed a great movement due to the increasing demographic growth, which led to the distortion of the urban fabric and the spread of chaotic structures, which led the Algerian legislator to enact tools and mechanisms to control this matter, and among the most important of these mechanisms is the building permit, which is one of the most important means Effective and effective in organizing construction operations, preserving the urban fabric and protecting the environment from all risks resulting from poor urban planning.